Erasmus of Rotterdam and his Approach to Tolerance - Matula, Jozef (Aither, 2020)
The main focus of the article is to study two of Erasmus' approaches to tolerance that are connected with the vision of unity and peace and the humanistic emphasis on dialogue. The justification of tolerance, which is most typical for Christian humanism as a whole, is to be found in many of Erasmus' works. Attention is initially paid to Erasmus' understanding of tolerance on the background of his central concept of philosophia Christi and around his antidogmatic and tolerant concept of Christianity. Tolerance is fundamentally connected to ideas about religious peace, piety and concord (pax, pietas, concordia). Tolerance also represents for Erasmus the beginning of self-mastery in the sense of enduring the differences and respecting the opinions and practices of others. Self-mastery is a prerequisite for a true dialogue. This does not mean unlimited tolerance for all opinions but a peaceful and moderate dialogue between opponents. This kind of dialogue is a necessity for the search for truth.